2011
DOI: 10.1016/j.psychsport.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A research agenda to examine the efficacy and relevance of the Transtheoretical Model for physical activity behavior

Abstract: Regular physical activity (PA) decreases the risk of several chronic diseases including some cancers, type II diabetes, obesity, and cardiovascular disease; however, the majority of US adults are not meeting the recommended levels to experience these benefits. To address this public health concern, the underlying mechanisms for behavior change need to be understood, translated and disseminated into appropriately tailored interventions. The Transtheoretical Model (TTM) provides a framework for both the conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 55 publications
(69 reference statements)
2
81
0
4
Order By: Relevance
“…The stage distribution of subjects in this study is similar to those in studies exploring the application of the transtheoretical model with other healthy 24 and clinical populations, 20 including those with respiratory disease. 25 In the majority of studies, most subjects report that they were in either a preparation or maintenance stage.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The stage distribution of subjects in this study is similar to those in studies exploring the application of the transtheoretical model with other healthy 24 and clinical populations, 20 including those with respiratory disease. 25 In the majority of studies, most subjects report that they were in either a preparation or maintenance stage.…”
Section: Discussionsupporting
confidence: 64%
“…23 It has been suggested that cognitive processes are utilized more during movement around the earlier stages of change (pre-contemplation to contemplation or preparation) and that behavioral processes are utilized more during movement around the later stages of change (preparation for action or maintenance). 23 However, a research agenda paper on the transtheoretical model 24 reported that previous research that has explored the application of the transtheoretical model in healthy populations has been subject to methodological limitations, such as the use of subjective methods of measuring physical activity, and very few have examined all constructs of the model. Also, a systematic review of transtheoretical model-based physical activity behavior change interventions conducted in various populations reported that the majority of interventions purported to be based on the transtheoretical model failed to accurately represent all dimensions of the model.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…The transtheoretical model (TTM) from Prochaska et al [41] is a behavior change model that is arguably well suited for use in a behavior change system, because it provides a framework for the conceptualization of behavior change and for the measurement of change, and strategies to promote change [37]. There are two main concepts in the TTM: the stages of change and the processes of change (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In reviews, physical activity intentions have been strongly associated 460 20 with physical activity behaviour (McEachan et al, 2011;Nigg et al, 2011). Therefore, 461 it remains important to listen to the voices of school students regarding their 462 experiences within PE.…”
mentioning
confidence: 99%